TRADISI BEBANGAR PADA MASYARAAKAT ETNIS SASAK DI DESA BAREJULAT - Nurohmah, Siti Dhia; Kaler, I Ketut; Alffiati, Alffiati (Jurnal Mahasiswa Antropologi dan Sosiologi Indonesia (JuMASI), 2024)
In the current modern era, the Sasak ethnic community in Barejulat Village still maintains the traditions of their ancestors, namely the bebangar tradition. Bebangar is a tradition carried out by the Sasak ethnic community when members of the community will use a piece of land to build a house, dig wells, open agricultural land, and so on. So the purpose of this study is to find out the motivation of the Sasak ethnic community in Barejulat Village to carry out the bebangar tradition. This study uses the theory of ceremony offerings from Robetson Smith and uses a qualitative approach with ethnographic methods. The results of this study found several factors that motivated the Sasak ethnic community in Barejulat Village to still carry out this tradition, including the strong influence of the local 'sasak boda' belief system about guardian spirits and ancestral spirits, cultural factors, and people's views of homes, wells, and agricultural land as a source of life.